Nilai-Nilai Kebangsaan pada Organisasi Ikatan Pelajar Muhammadiyah dan Ikatan Pelajar Nahdlatul Ulama Provinsi Lampung - Nurkholis, Nurkholis; Syahid, Akhmad (Tapis: Jurnal Penelitian Ilmiah, 2023)
Nahdlatul Ulama and Muhammadiyah are organizations that have a large number of members, so an appropriate formula is needed to unify perceptions of how the nation and state live, and how efforts are made to fortify its members from the influence of the swift currents of globalization, including their students. Based on this, the authors are interested in conducting research to find out about the implementation of national values ​​in NU and Muhammadiyah students in Lampung Province. This study uses a type of qualitative research, and uses two data sources, namely primary data and secondary data. Primary data were obtained directly from education managers within NU and Muhammadiyah, NU and Muhammadiyah administrators and students. Secondary data is obtained from documents in the form of books, brochures, reports and so on. After the data is collected, the data is analyzed using qualitative data analysis techniques with inductive thinking methods and descriptive analysis. The national values ​​of NU and Muhammadiyah students look quite good and can influence the mindset of students, including by increasing a high sense of nationalism and always maintaining unity and oneness. This implementation can be seen in the existence of material on understanding national values, which is always carried out either directly or indirectly in every activity. The national values ​​given include religion, kinship, mutual cooperation, tolerance between religious communities and fellow religious people and always maintaining the unity and integrity of the nation.